Study on Nano Drug Particles in the Diagnosis and Treatment of Alzheimer’s Disease in the Elderly - ChangQing Li; Yu Xiang; Yunqian Wang; Ping Li (Bioinorganic Chemistry and Applications)
Objective. To study the clinical effect of nano drug particles in the diagnosis and treatment of Alzheimer’s disease in the elderly, we promote the research on the treatment of Alzheimer’s disease and provide basis. Methods. 80 patients with Alzheimer’s disease treated in our hospital from April 2021 to April 2022 were selected as the research objects and were divided into the reference group and the observation group by random number table method. The reference group was given traditional treatment drugs, and the observation group was given nano drug particles. The treatment effect, blood lipid level, cognitive function status, and comprehensive effective rate of the two groups were compared, and the treatment data of the patients were scored by ADL and MMSE scale to understand the intelligence level and daily living ability of the patients. Results. From the comparison results, it is found that the blood lipid level of the control group was in the normal range. The cognitive function of the control group was also better than that of the reference group. The scores of ADL and MMSE in the control group were higher than those in the reference group. The effective rate of the control group was also higher than that of the reference group; P<0.05, with statistical significance. Conclusion. In the diagnosis and treatment of Alzheimer’s disease in the elderly, nano drug particles have good stability and less toxic and side effects, improve the ability of daily living of patients, and have good clinical treatment effect, which is worthy of clinical application.